1998
DOI: 10.1159/000006532
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin Innervation of the Cerebral Cortex in a Reptile, the Lizard <i>Psammodromus algirus</i>

Abstract: We used light and electron microscopic and immunohistochemical methods to map the distribution of cholecystokinin (CCK) in the cerebral cortex of a lizard, Psammodromus algirus. At light microscopy, the CCK immunoreactivity was limited to fibers and terminals densely innervating all cortical regions except for the lateral (pyriform) cortex which was very slightly immunostained. The CCK-positive terminals were almost restricted to the cell layers in every cortical region where they surrounded immunonegative cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…These cases show retrograde labeling of cells in the dorsal cortex. Guirado et al [1998] also showed one experiment in a lizard, in which HRP was injected precisely within the area now deduced to be the reptilian LPall [Puelles et al, 2016a. Retrogradely labeled cells appeared distinctly within the whole dorsal cortex (their Fig.…”
Section: Connectivity Of the Claustro-insular Lpall With Thoughts Onmentioning
confidence: 92%
“…These cases show retrograde labeling of cells in the dorsal cortex. Guirado et al [1998] also showed one experiment in a lizard, in which HRP was injected precisely within the area now deduced to be the reptilian LPall [Puelles et al, 2016a. Retrogradely labeled cells appeared distinctly within the whole dorsal cortex (their Fig.…”
Section: Connectivity Of the Claustro-insular Lpall With Thoughts Onmentioning
confidence: 92%
“…5,11). In contrast, the DVR of reptiles seems to present mainly a VPall bulge, or separately bulging VPall and LPall sectors, and the LPall may bulge only transiently (Kuhlenbeck, 1927(Kuhlenbeck, , 1973(Kuhlenbeck, , 1977Schepers, 1948;Striedter, 1997;Guirado et al, 1998;Bruce, 2007;Suzuki and Hirata, 2014;Fig. 11).…”
Section: Lpallmentioning
confidence: 99%
“…118 In these plants foraging by insects facilitates dispersal of pollen grains in the air but the may not actually pollinate the flowers. 120 In closed tropical conditions wind pollination may not always correlate completely with anemophilous syndrome. 120 In closed tropical conditions wind pollination may not always correlate completely with anemophilous syndrome.…”
Section: Wind Pollinationmentioning
confidence: 99%
“…27,11 8 Anatomically, reptilian dorsal cortex resembles with the isocortex of mammals in many respect. The three neurons of reptilian dorsal cortex namely bitufted neurons, multipolar neurons and pyramidal neurons have formed the basis for comparing the medial aspect of dorsal cortex being homologous to the mammalian hippocampal formation, [119][120] whereas the lateral aspect of the dorsal cortex has been compared to the mammalian isocortex, or at least to part of it. 107,121 Anatomically the dorsal cortex of reptiles differ from the isocortex in being three layered instead of six layered and in lacking columnar organization.…”
Section: Comparison Of the Neuronal Types Of The Cerebral Cortex In Rmentioning
confidence: 99%